2020
DOI: 10.1534/genetics.120.303200
|View full text |Cite
|
Sign up to set email alerts
|

Growth-Dependent Activation of Protein Kinases Suggests a Mechanism for Measuring Cell Growth

Abstract: In all cells, progression through the cell cycle occurs only when sufficient growth has occurred. Thus, cells must translate growth into a proportional signal that can be used to measure and transmit information about growth. Previous genetic studies in budding yeast suggested that related kinases called Gin4 and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Although such regulation in M phase is known ( Leitao and Kellogg, 2017 ; Garmendia-Torres et al, 2018 ), our data suggest a sequential mechanism to match size to growth rate, with a nutrient-independent sizer followed by a nutrient-dependent timer. To detect the peak in bud growth generated by the sizer, cells may use Gin4-related kinases ( Jasani et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although such regulation in M phase is known ( Leitao and Kellogg, 2017 ; Garmendia-Torres et al, 2018 ), our data suggest a sequential mechanism to match size to growth rate, with a nutrient-independent sizer followed by a nutrient-dependent timer. To detect the peak in bud growth generated by the sizer, cells may use Gin4-related kinases ( Jasani et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study revealed that a pantothenate transporter gene disruption mutant could not form spores [ 33 ]. In some fungi, the serine/threonine-protein kinase Gin4 was important for the septin organization and cell cycle [ 34 , 35 , 36 ]. The inactivation of Gin4 led to a prolonged mitotic delay [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some fungi, the serine/threonine-protein kinase Gin4 was important for the septin organization and cell cycle [ 34 , 35 , 36 ]. The inactivation of Gin4 led to a prolonged mitotic delay [ 36 ]. In the RNA-seq data, the gene for the serine/threonine-protein kinase Gin4 (MAC_00865) was upregulated, which may accelerate the process of cell division, suggesting the possibility that MaOpy2 may regulate the expression of Gin4 to shift the conidiation pattern, thus promoting the conidiation—but this needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, we found additional evidence that membrane trafficking events that drive cell growth generate signals that are correlated with growth, which could be used to measure growth. For example, delivery of vesicles to the plasma membrane in growing daughter buds generates signals that lead to phosphorylation of the kinase Pkc1 as well as two related kinases called Gin4 and Hsl1 ( Anastasia et al, 2012 ; Jasani et al, 2020 ). In each case, multi-site phosphorylation of these kinases appears to gradually increase during bud growth, and phosphorylation is dependent upon growth and correlated with the extent of growth.…”
Section: Discussionmentioning
confidence: 99%